An unexpected finding after robotic subtotal gastrectomy: Vomiting of Taenia Saginata. (2020) - Albertini, Nicola; Pecchini, Francesca; Esposito, Sofia; Gozzo, Davide; Colli, Giovanni; Piccoli, Micaela
Highlights: Robotic subtotal gastrectomy with postoperative detection of parasitic infection. A rare case of parasitic infection. Diagnosis of gastric cancer hindered the suspicious of taeniasis. Abstract: Introduction: Most Human taeniasis are asymptomatic or associated with vague clinical manifestations, but cases of unusual migration of these parasites have been described. Presentation of a case: A case of challenging diagnosis of human Taenia Saginata infection is here presented: during COVID-19 pandemic we performed a mininvasive robotic subtotal gastrectomy for gastric angulus adenocarcinoma. 10 h after the end of the operation the patient presented an episode of vomiting with expulsion of a 5-meter-long adult form of Taenia Saginata . Discussion: Parasitic infections are more frequent in the developing countries; in our case the transposition of small intestinal loop surely promoted the migration of Taenia Saginata through the gastro-jejunal anastomosis into the gastric stump. Preoperative evaluation (history, physical examination and imaging features) led to gastric cancer diagnosis and hindered the recognition of the taeniasis because of similar clinical presentations and the need to start quickly a therapeutic oncological strategy. Conclusion: Even if these cases are exceptional especially in Western Europe, it is important to obtain a detail clinical history and exclude parasitic infection as a cause of loss of weight and gastrointesinal abnormalities.